Akurasi Sitologi Imprin dibandingkan Potong Beku terhadapHistopatologi Kelenjar Sentinel Karsinoma Payudara - Tjiok, Sufida - (Universitas HKBP Nommensen, 2024)
ABSTRACT Background: Sentinel lymph node is the initial site of tumor cell metastasis from the breast before to other organs. To help make an accurate diagnosis and identify metastases, an intraoperative sentinel lymph node biopsy is performed for imprint cytology, frozen section and histopathological examination. Objective: Knowing the comparison the accuracy of imprint cytology,frozen section with histopatology in sentinel lymph node nodule tissue from breast carsinoma patients at Murni Teguh Hospital Medan in 2018-2020. Methods: This study uses a retrospective analysis with cross-sectional design, a total sample of 44 breast cancer patient’s sentinel lymph nodes are examined sentinel lymph nodes with imprint cytology, frozen section and histopatoloy fulfill inclusion criteria, then McNemar test is carried out. Results: The result of imprint cytology, frozen section and histopatology. Imprint cytology accuracy 95%, sensitivity 100%, specificity 90%, positive predictive value 92,3%, negative predictive value 100%. While the frozen section accuracy value 97,75%, 100% sensitivity, 95% specificity, 96% positive predictive value, 100% negative predictive value. McNemar test results on imprint cytology with histopathology obtained a p-value of 0.500 and frozen section with histopathology obtained a p-value of 1.000, meaning there is no significant difference result between imprint cytology and frozen section at Murni Teguh Hospital Medan in 2018 -2020. Conclusion: There is no significant difference result between imprint cytology and frozen section at Murni Teguh Medan Hospital in 2018-2020. Imprint cytology examination can use as alternative to frozen section in area with limited facilities for making intra operative decision. Keywords: Imprint cytology, frozen section, sentinel lymph node, breast cancer. ABSTRAK Latar belakang: Kelenjar getah bening sentinel merupakan tempat awal metastasis sel tumor dari payudara sebelum ke organ lain. Untuk membantu menegakkan diagnosis secara akurat dan mengetahui metastasis dilakukan biopsi intraoperatif kelenjar getah bening sentinel untuk pemeriksaan sitologi imprin, potong beku dan histopatologi. Tujuan: Mengetahui perbandingan akurasi sitologi imprin terhadap histopatologi potong beku pada jaringan nodul sentinel kelenjar getah bening dari pasien karsinoma payudara di RS Murni Teguh Medan Tahun 2018-2020. Metode: Penelitian ini menggunakan analitik retrospektif dengan desain cross-sectional, jumlah sampel sebanyak 44 pasien karsinoma payudara yang dilakukan pemeriksaan pada kelenjar getah bening sentinel dengan sitologi imprin, potong beku dan histopatologi serta memenuhi kriteria inklusi untuk dilakukan Uji McNemar. Hasil: Hasil penelitian dari pemeriksaan sitologi imprin, potong beku dan histopatologi. Memperoleh akurasi pemeriksaan sitologi imprin 95%, sensitivitas 100%, spesifisitas 90%, nilai prediksi positif 92,3%, nilai prediksi negatif 100%. Sedangkan potong beku nilai akurasi 97,75% sensitivitas 100%, spesifisitas 95% nilai prediksi positif 96%, nilai prediksi negatif 100%. Hasil Uji McNemar pada sitologi imprin dengan histopatologi didapatkan p-value 0,500 dan potong beku dengan histopatologi didapatkan p-value 1,000 artinya tidak terdapat perbedaan signifikan antara sitologi imprin dibanding potong beku di RS Murni Teguh Medan Tahun 2018-2020. Kesimpulan: Tidak terdapat perbedaan bermakna antara pemeriksaan sitologi imprin dan potong beku di RS Murni Teguh Medan 2018-2020, sehingga sitologi imprin dapat digunakan sebagai alternatif pengganti pemeriksaan potong beku pada daerah yang memiliki keterbatasan fasilitas untuk menegakan diagnosis. Kata Kunci: Sitologi imprin, potong beku, kelenjar getah bening sentinel, karsinoma payudara.